Comparison of Acetabular Morphology between Femoral Neck and Intertrochanteric Fractures - Sahin, Erdem; Turgut, Mehmet Cenk; Zeynel, Alperen (Cerrahpaşa Medical Journal, 2023)
Objective: This study aimed to examine the correlation between acetabular morphology and fractures of the proximal femur. Methods: In this retrospective study, we examined patients who were admitted to our hospital between 2017 and 2021 due to fractures in the neck and intertrochanteric regions of the femur. The study included 192 patients with intertrochanteric fractures (Group 1) and 61 patients with femoral neck fractures (Group 2). Various parameters such as age, gender, Body Mass Index (BMI), acetabular index (AI), acetabular depth (AD), and cortical index (CI) were assessed and analyzed. Results: Group 1 exhibited a significantly greater mean age compared to Group 2 (p=0.001). The two groups showed similar distributions in terms of gender and BMI. There were no significant differences observed in the acetabular depth (AD) and cortical index (CI) values between the groups. However, Group 1 displayed a significantly higher acetabular index (AI) compared to Group 2 (p=0.01). Conclusion: According to our study findings, it is evident that there exists an association between proximal femoral fractures and acetabular morphology.